2019
DOI: 10.1128/aac.01536-19
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induction by a Small Molecule Inhibits Salmonella Survival in Macrophages and Mice

Abstract: Salmonella enterica is a natural bacterial pathogen of humans and animals that causes systemic infection or gastroenteritis. During systemic infection, Salmonella generally resides within professional phagocytes, typically macrophages, whereas gastroenteritis is caused by infection of epithelial cells. We are only beginning to understand which host pathways contribute to Salmonella survival in particular cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
4
18
0
Order By: Relevance
“…We used a fluorescence-based cell culture assay to identify compounds with non-traditional antimicrobial capabilities from chemical and drug libraries. This approach uncovered inhibitors of bacterial efflux pumps, a stimulator of macrophage autophagy and an antibiotic used against Mycobacterium species that was unexpectedly potent against Gram-negative bacteria during infection [21,22,25]. Within the current work, we examined the mechanism of action of a compound identified by SAFIRE, JD1, that strongly reduces S. Typhimurium replication in macrophages and disrupts the bacterial cell membrane upon breaching the outer membrane barrier.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a fluorescence-based cell culture assay to identify compounds with non-traditional antimicrobial capabilities from chemical and drug libraries. This approach uncovered inhibitors of bacterial efflux pumps, a stimulator of macrophage autophagy and an antibiotic used against Mycobacterium species that was unexpectedly potent against Gram-negative bacteria during infection [21,22,25]. Within the current work, we examined the mechanism of action of a compound identified by SAFIRE, JD1, that strongly reduces S. Typhimurium replication in macrophages and disrupts the bacterial cell membrane upon breaching the outer membrane barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Female C57Bl/67–8-week-old mice were intraperitoneally (IP) inoculated with 8 x 10 3 CFU, and the infectious dose was verified by plating for CFU. Mice were IP-treated with 100 μL of vehicle (70% DMSO) or 1 mg/kg of JD1 in 100 μL of vehicle at 10 minutes and 24 hours post-infection based on a previously established protocol [ 22 ]. Dosages were extrapolated from LDH toxicity and SAFIRE IC 50 assays, according to approved IACUC protocols [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AR-12 microcapsules, prepared using a novel degradable acetalated dextran (Ac-Dex) biopolymer, further enhanced the clearance of intracellular Salmonella and significantly reduced drug toxicity (Hoang et al, 2014). In order to identify small molecules capable of interfering with Salmonella survival or replication in macrophages, Nagy et al (2019) screened the 14,400-compound Maybridge HitFinder v11 library in a high-content Screen for Anti-Infectives. They found that one small molecule, D61, reduced Salmonella load both in vitro and in vivo, through its autophagy-stimulating activity.…”
Section: Certain Drugs Regulate Xenophagy To Combat Salmonella Infectionmentioning
confidence: 99%